Traditional medicinal plants in Barangay Dagbasan, Mabinay, Philippines: an ethnobotanical documentation of local knowledge and practices - Sari, Wahyu Wido; Baena, Alexander S. (Acta Biochimica Indonesiana, 2025)
Background: Traditional medicinal plants constitute an essential component of primary healthcare in rural Philippine communities, yet systematic documentation remains limited in many regions. Objective: This study aimed to document traditional healing practices utilizing medicinal plants in Barangay Dagbasan, Mabinay, Negros Oriental, Philippines, identifying plant species used for various ailments, commonly used plant parts and preparation methods, and pathways of traditional knowledge transmission. Methods: A qualitative ethnobotanical approach employing rapid ethnographic assessment was conducted through semi-structured interviews, participatory demonstrations, and guided field walks. Data were analyzed using thematic analysis with frequency counts for plants, ailments, plant parts, and preparation methods. Results: Thirty-three biomedicinal plant species were documented, including several Philippine Department of Health-approved plants. The most commonly treated ailments were cough (15%), wounds (15%), stomachache (9%), fever (8%), and diarrhea (7%). Leaves were the most frequently utilized plant part (56%), with preferred preparation methods being topical application (23%), ingestion (21%), and decoction (13%). Conclusion: Barangay Dagbasan maintains rich ethnobotanical traditions providing essential healthcare access. However, limited knowledge about certain plant parts, external knowledge contamination through social media, and conservation concerns necessitate interventions including pharmacological validation, conservation programs, and educational initiatives to preserve traditional knowledge while ensuring sustainable medicinal plant use.